ANALISIS PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK SEKOLAH MENENGAH KEJURUAN - Ridho Suharis (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts is one of the abilities that must be owned by students in learning mathematics.Based on observations that have been do, understanding of mathematical concept students of grade X C SMK Negeri 2 Padang was low. The solution to overcome the problem is learning by using model cooperative learning tipe Think Pair Share. This research is a quasi-experimental research design with static group design. The populations were students of grade X C with grade X C3 as an experimental class and grade X C1 as a control class. Instruments used in this research is a test of understanding of the concept students. The results showed that the understanding of mathematical concepts students who learn by using model cooperative learning tipe Think Pair Share is better than the understanding of mathematical concepts students who learn by using direct learning in class X C SMK Negeri 2 Padang.Keywords – Understanding Of Mathematical Concepts, Think Pair Share , Direct